(338) Regional Economic Planning. - Hammam, Ezz El-Din. (The Institute Of National Planning., 2018)
regional planning is one of three dimensions which must be taken into consideration by the plan makers in planning for the development of resources in a country for the sake of reducing inequalities which may exist between its various regions. thus regional planning is a dimension of planning which takes into consideration space and location factors.